Trends in the development of accessibility to civil rights protection - Sheremetyeva Anna Konstantinovna; Kalacheva Tatyana Leontievna; Makharadze Natalia Sergeevna; Parfenov Konstantin Borisovich; Fadeeva Antonina Viktorovna (SHS Web of Conferences, 2021)
The purpose of the study is to analyze the legal regulations that cover the procedures for resolving disputes without judicial proceedings for their subsequent development and popularization. In the course of the study, in combination with a comprehensive and systematic analysis, the following general scientific cognition methods were used: dialectical, hermeneutic, synthesis, the method of ascending from the abstract to the concrete, the method of generalization and comparison. The results of the study are as follows: justice, being a necessary element of building the rule of law, should be supplemented and improved through alternative ways of resolving conflict situations. The latter shall develop civil jurisdiction and resolve disputes on a highly professional basis. It seemed that the creation of a single procedural form would be a guarantee of the effectiveness of the protection of rights, but in contrast to this idea, there was created a procedural code that regulates administrative jurisdiction. In this regard, it seems promising to develop alternative dispute resolution mechanisms, which are simpler models of protection of violated interests than the court. Therefore, the novelty of the study is in the justification of the need to identify patterns of improving access to legal protection through the use of alternative methods of dispute resolution.